Batek tribe: entrepreneurship in perspective / Mohd Amli Abdullah … [et al.] - Abdullah, Mohd Amli; Abd Mutalib, Muhammad Zahran; Ahmad, Badli Esham; Ismail, Mohd Rozaidi (2018)
A study was conducted on the Batek tribe in Taman Negara, Pahang. The study was aimed at exploring the contribution of the Batek tribe in entrepreneurship activities among them. An expedition assisted by a local guide was conducted in Taman Negara, Jerantut, Pahang, Malaysia where a few small and medium sized communities of Batek live. Interviews were conducted with some of the Batek men to understand their entrepreneurship activities. Observation was also used as evidence in exploring their entrepreneurship activities. The expedition was led by local guide who has a close relationship with the Batek headman and is also proficient in their language. Three settlements are identified; Kampung Lubuk Ceruk or also known as Seberang Kanopi. Kampung Aur and Kampung Rinching. The study intends to look at the type of business that the Batek were involved in as well as the motive behind their involvement. The study found that the Batek were involved in handicraft as well as becoming personal tourist guides. The main motive for their involvement is to provide adequate resources during monsoon seasons. The study concludes by suggesting a few ways to improve the entrepreneurial activities for the Batek.